Sustainable development of national green innovation capacity: a qualitative comparative analysis based on dynamic public data - Ran, Yi; Qijia, Liu (Frontiers in Public Health, 2025)
IntroductionIn the context of intensified global climate change and increasing environmental constraints, green innovation has emerged as a critical pathway for promoting sustainable national development. As leading economies in Asia, China, Japan, and South Korea have demonstrated distinct approaches to green innovation, making them valuable cases for comparative study. This study aims to identify key factors and configuration paths influencing the sustainable development of national green innovation.MethodsUsing the Qualitative Comparative Analysis (QCA) method and national-level public data, this research constructs multi-factor configurational models to examine how government policy, R&D investment, clean energy supply and demand, renewable energy share, and environmental greening collectively impact green innovation performance. Robustness checks and country-specific coverage analyses were conducted to ensure the reliability of the findings.ResultsThe results reveal three dominant configurations driving green innovation: (1) the synergy between government leadership and R&D investment; (2) dual-driven paths combining clean energy supply and demand; and (3) a synchronized increase in renewable energy share and environmental greening. Country-specific analysis shows that Japan aligns most closely with the first configuration, reflecting its emphasis on industrial structure and policy-driven innovation. China exhibits strong compatibility with the second configuration, highlighting its diversified strategy and market-based mechanisms. South Korea demonstrates the highest coverage in the third configuration, emphasizing clean energy supply and urban greening efforts.DiscussionThis study concludes that sustainable green innovation development depends on the synergy of multiple factors, and that countries should tailor their strategies based on national resource endowments and policy orientations. The research contributes to the literature by extending the configurational approach to green innovation and offers practical insights for designing differentiated and effective green development policies.